2016
DOI: 10.1097/inf.0000000000001217
|View full text |Cite
|
Sign up to set email alerts
|

Ten-Year Study of the Stringently Defined Otitis-prone Child in Rochester, NY

Abstract: This review summarizes a prospective, longitudinal 10-year study in Rochester NY with virtually every clinically diagnosed acute otitis media (AOM) confirmed by bacterial culture of middle ear fluid. Children experiencing 3 episodes within 6 months or 4 episodes in 12 months were considered stringently-defined otitis prone (sOP). We found stringent diagnosis compared with clinical diagnosis reduced the frequency of children meeting the OP definition from 27% to 6% resulting in 14.8% and 2.4% receiving tympanos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 23 publications
0
32
0
Order By: Relevance
“…Whenever the children were diagnosed as having AOM, tympanocentesis was performed and MEF samples were collected to confirm the clinical diagnosis. When a child experienced 3 episodes of AOM infections within a 6 month time span or 4 episodes of AOM infections in a 12 month time span they were designated as AOM infection-prone and because the diagnosis was confirmed by tympanocentesis-derived middle ear fluid culture we have termed these children stringently-defined otitis prone in our prior publication (20). Three bacterial pathogens ( Spn, NTHi and Mcat ) were identified by culture.…”
Section: Methodsmentioning
confidence: 99%
“…Whenever the children were diagnosed as having AOM, tympanocentesis was performed and MEF samples were collected to confirm the clinical diagnosis. When a child experienced 3 episodes of AOM infections within a 6 month time span or 4 episodes of AOM infections in a 12 month time span they were designated as AOM infection-prone and because the diagnosis was confirmed by tympanocentesis-derived middle ear fluid culture we have termed these children stringently-defined otitis prone in our prior publication (20). Three bacterial pathogens ( Spn, NTHi and Mcat ) were identified by culture.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, our published studies show that about 90% of otitis prone children have inadequate innate responses and diminished quantity and function of antibody generated to pneumococcal proteins, diminished memory B- and T-cell generation, and specific deficits in activation of B-cells and helper T-cells. [76] Many of these children also show an increased propensity to viral URI and fail to generate protective anti-viral antibody following infection[77] indicating broad immunologic defects. About 25% of otitis-prone children fail to produce immune responses when antigen is presented by injection of routine pediatric vaccines.…”
Section: Pneumococcal Protein Vaccines To Prevent Acute Otitis Mediamentioning
confidence: 99%
“…Over the past 10 years, we have studied a large population of children during their first 3 years of life who experience repeated pneumococcal infections in the middle ear, sinuses and lungs. [76,87] Our research has identified deficiencies in T and B cell immunity in response to pneumococcal infections. [88,89] The deficiencies resemble a neonatal immunity response, giving our group reason to propose a new type of immunodeficiency termed “Prolonged Neonatal-Like Immune Profile” (PNIP).…”
Section: Expert Commentarymentioning
confidence: 99%
See 2 more Smart Citations